Individual Characteristics and Organizational Factors Related to Patient Safety Culture at Regional General Hospital X, East Tanjung Jabung Regency in 2025 - Sartika, Yuli Maya; Guspianto, Guspianto; Muldiasman, Muldiasman; Amir, Andy; Kalsum, Ummi; Eka Rini, Willia Novita; Asparian, Asparian (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Patient safety culture is an important indicator of service quality and safety in hospitals. A low level of patient safety culture implementation may increase the risk of patient safety incidents. This study aimed to analyze individual and organizational factors associated with the implementation of patient safety culture at RSUD X, Tanjung Jabung Timur Regency. Objective: . The study population consisted of 340 individuals, with a sample of 198 respondents selected using proportionate stratified random sampling. Method: This study employed a quantitative cross-sectional design. Result and Discussion: The results showed that patient safety culture at RSUD X remained at a low level, with a mean score of 67.65. Bivariate analysis indicated significant associations between gender, employment status, and educational level with patient safety culture, as well as between leadership and management systems with patient safety culture. Multivariate analysis revealed that gender, employment status, education, leadership, training, management systems, and safety climate were associated with the implementation of patient safety culture, with education identified as the dominant factor after controlling for other variables., Conclusions: : Strengthening human resource capacity and continuously improving organizational factors are necessary to enhance patient safety culture in hospitals